Parametric analyses for the calculation of vulnerability scores used in rapid visual screening of 3D RC frame structures with an energy-based method - Demirbas, Nurbanu; Sahin, Humeyra; Durucan, Cengizhan (Elsevier Sci Ltd, 2026)
In this study, the vulnerability scores (VSs) associated with various structural deficiencies, commonly used in Rapid Visual Screening (RVS) methods, were comprehensively re-evaluated using three-dimensional reinforced concrete structural models by an energy-based approach. In the evaluations, two different cases were considered in calculating the VSs of structural deficiencies; (i) the case where structural deficiencies present discretely and (ii) the case where some structural deficiencies present combined. In the first scenario, the discrete effects of each structural deficiency, and VSs were obtained for soft/weak-story, torsional effect, heavy overhang, and pounding effect deficiencies. Second scenario focused on the combined effects of the soft-story deficiency with the other deficiencies considered in the study and VSs were obtained for the combined effect. In addition to these assessments, the structural models were analyzed in relation to the degree of structural deficiencies and the number of stories. From the numerical study; (i) for the VSs obtained from the discrete effects of structural deficiencies, it was observed that high VS values were obtained for soft-story, torsional effect and pounding deficiencies types, and (ii) the VSs obtained for the combined effects of structural deficiencies are generally lower than the total VS obtained by summing the VS obtained from the discrete effects of associated deficiencies, which are calculated in a similar approach to that commonly used in RVS methods. It is generally observed that the soft-story deficiency is the most significant deficiency type on the VSs derived from the combined effects.
Keywords: Soft/Weak-Story; Torsional Effect; Heavy Overhang; Pounding Effect; Rapid Assessment Method; Nonlinear Time History Analysis; Nonlinear Pushover Analysis